COMPARATIVE STUDY OF RESPONSIBILITY OF CRIMINAL VIOLENCE IN HOUSEHOLD IN CONCEPT POSITIVE LAW AND MINANGKABAU TRADITIONAL LAW - Azriadi Azriadi; Mahlil Adriaman (JCH (Jurnal Cendekia Hukum), 2021)
Domestic Violence (KDRT) is a form of crime in the domestic sphere; the data on domestic violence is increasingly worrying and tends to be out of control. Based on the Records of Violence against Women (CATAHU) in 2019; there were 431,471 cases of violence against women and it has been escalated up to 693% since 2008 which was only 54,425 cases. The effort to overcome and handle domestic violence is carried out by formulating various kinds of laws and regulations, creating structural and non-structural institutions that handle domestic violence cases, but in reality acts of violence continue to increase. In West Sumatra, Minangkabau customary law is prevailed as a law that is admited by the constitution. In fact domestic violence in Minangkabau society is a common problem. In handling and overcoming domestic violence, positive law and Minangkabau customary law have their own ways. From the data of national statistics agency of indoensia (BPS) in 2019, West Sumatra was not classified as the 10 highest occurrences of domestic violence in Indonesia. Based on this phenomenon, it is very interesting to study and to be compared of the effort to overcome domestic violence based on the concepts of Positive Law and Minangkabau Customary Law. This study uses a normative approach, namely examining library materials or secondary data consisting of primary legal materials and tertiary legal materials. The results of Positive Law research in overcoming domestic violence focus on handling by applying the law with maximum punishment (repressive), by providing education to the community that is directed and well programmed (preventive), even if domestic violence occurs then efforts are made (pre-emptive) so that the impact or the consequences are not significant. While Minangkabau customary law is more of a preventive effort, namely before the occurrence of domestic violence and the application of Minangkabau customary law is carried out in stages based on the proverb Bajanjang Naik Batanggo Turun.